1976
DOI: 10.1071/bi9760405
|View full text |Cite
|
Sign up to set email alerts
|

The Conformational Stabilities of Tropomyosins

Abstract: The stability to denaturation by heat and guanidine hydrochloride of seven vertebrate (including skeletal, cardiac and smooth muscle) tropomyosins and three invertebrate tropomyosins was examined. The transition profiles were discontinuous and in many cases distinct plateaux were observed which indicated the presence of unique partially unfolded states at intermediate temperatures and guanidine hydrochloride concentrations.The denaturation by guanidine hydrochloride could be described in the majority of cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

1977
1977
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 31 publications
6
22
1
Order By: Relevance
“…Eckard and Cowgill (1976) have examined fragments produced by the tryptic digestion of rabbit tropomyosin and found that the C-terminal portion of the molecule was the most stable part. This is contrary to predictions on molecular stability deduced from the (X-helix-favouring potential of the amino acids (Woods 1976) and also contrary to some other experimental evidence (parry 1975). This paper reports the separation and characterization of fragments of (X-tropomyosin prepared by and Woods 1971).…”
Section: Introductioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Eckard and Cowgill (1976) have examined fragments produced by the tryptic digestion of rabbit tropomyosin and found that the C-terminal portion of the molecule was the most stable part. This is contrary to predictions on molecular stability deduced from the (X-helix-favouring potential of the amino acids (Woods 1976) and also contrary to some other experimental evidence (parry 1975). This paper reports the separation and characterization of fragments of (X-tropomyosin prepared by and Woods 1971).…”
Section: Introductioncontrasting
confidence: 55%
“…He found that predictions on stability from the gross amino acid composition did not correlate with the observed stabilities to denaturation by heat and guanidine hydrochloride. The strength of the hydrophobic and electrostatic interactions between the two strands of the coiled-coil structure would need to be taken into account in order to predict the molecular stability (Woods 1976). The unstaggered coiled-coil structure (McLachlan and Stewart 1975) allows close packing of the non-polar side chains of the two helices and this arrangement also allows favourable interactions between positive and negative charges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This need not involve a gross reduction in helical content. Evidence obtained using several techniques demonstrates that vertebrate striated muscle TMs undergo stepwise denaturation (Woods, 1976;Lehrer, 1978;Graceffa and Lehrer, 1980;Edwards and Sykes, 1980;Williams and Swenson, 1981 ;Potekhin and Privalov, 1982;Betteridge and Lehrer, 1983). A partial unfolding event, propagated through the coiled coil of the fast isoform to the overlap site (Edwards and Sykes, 1980), could account for the data collected at 25°C.…”
Section: S E S L K D a Q E K L E V A E K T A T D 80 A E A D V A S L Nmentioning
confidence: 99%